Fiscal expenditure spillovers in the euro area: An empirical and model-based assessment - Mario Alloza; Marien Ferdinandusse; Pascal Jacquinot; Katja Schmidt (European Central Bank (ECB), 2020)
The paper describes the main transmission channels of the spillovers of national fiscal policies to other countries within the euro area and investigates their magnitude using different models. In the context of Economic and Monetary Union (EMU), fiscal spillovers are relevant for the accurate assessment of the cyclical outlook in euro area countries, as well as in the debates on a coordinated change in the euro area fiscal stance and on a euro area fiscal capacity. The paper focuses on spillovers from expenditure-based expansions by presenting two complementary exercises. The first is an empirical investigation of spillovers based on a new, long quarterly dataset for the largest euro area countries and on new estimates based on annual data for a panel of 11 euro area countries. The second uses a multi-country general equilibrium model with a rich fiscal specification and the capacity to analyse trade spillovers. Fiscal spillovers are found to be heterogeneous but generally positive among euro area countries. The reaction of interest rates to fiscal expansions is an important determinant of the magnitude of spillovers.
Keywords: F42; F45; H50; E62; E63; 330; fiscal spillovers; fiscal policy; monetary policy; VAR; DSGE